Evidence for the Utility of Actuarial Neuropsychological Criteria Across the Continuum of Normal Aging, Mild Cognitive Impairment, and Dementia - Graves, Lisa V. (J Alzheimers Dis, 2020)
BACKGROUND: Research suggests that actuarial neuropsychological criteria improve the accuracy of mild cognitive impairment (MCI) diagnoses relative to conventional diagnostic methods. OBJECTIVE: We sought to examine the utility of actuarial criteria relative to consensus diagnostic methods used in the National Alzheimer’s Coordinating Center (NACC) Uniform Data Set (UDS), and more broadly across the continuum of normal aging, MCI, and dementia. METHODS: We compared rates of cognitively normal (CN), MCI, and dementia diagnoses at baseline using actuarial versus consensus diagnostic methods in 1524 individuals from the NACC UDS. RESULTS: Approximately one-third (33.59%) of individuals diagnosed as CN and more than one-fifth (22.03%) diagnosed with dementia based on consensus methods, met actuarial criteria for MCI. Many participants diagnosed with MCI via consensus methods also appeared to represent possible diagnostic errors. Notably, the CN(a)/CN(c) group (i.e., participants diagnosed as CN based on both actuarial [(a)] and consensus [(c)] criteria) had a lower proportion of apolipoprotein E ɛ4 carriers than the MCI(a)/MCI(c) group, which in turn had a lower proportion of ɛ4 carriers than the dementia (Dem)(a)/Dem(c) group. Proportions of ɛ4 carriers were comparable between the CN(a)/CN(c) and CN(a)/MCI(c), MCI(a)/MCI(c) and MCI(a)/CN(c), MCI(a)/MCI(c) and MCI(a)/Dem(c), and Dem(a)/Dem(c) and Dem(a)/MCI(c) groups. These results were largely consistent with diagnostic agreement/discrepancy group comparisons on neuropsychological performance. CONCLUSION: The present results extend previous findings and suggest that actuarial neuropsychological criteria may enhance diagnostic accuracy relative to consensus methods, and across the wider continuum of normal aging, MCI, and dementia. Findings have implications for both clinical practice and research.